RELATIONSHIP OF POST TRAUMATIC GROWTH PSYCHOLOGICAL DISTRESS AND QUALITY OF LIFE AMONG RENAL FALIURE PATIENTS - Ehsan, Neelam; ., Nayab; Khan, Adam; Shahid, Amna Khan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the relationship and impact of post traumatic growth and psychological distress on qualityof life among renal failure patients seeking dialysis, and to see differences in these variables among different age group patients.Study Design: Cross sectional study.Place and Duration of Study: Lady Reading Hospital, Peshawar, Government Hospital Mardan Pakistan, fromJan to Jun 2019.Methodology: A sample of 300 renal failure Patients 18 years or older who had a diagnosis of end-stage renal disease receiving treatment within different dialysis units were approached through purposive sampling technique. Post traumatic growth inventory Quality of life scale and the Psychological distress scale were used to measure the study variables.Results: Results reveal that psychological distress has a negative correlation with post traumatic growth (r=-0.77**, p